2018
DOI: 10.1371/journal.pone.0194993
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in epithelial ovarian cancer: A population-based study

Abstract: The overall survival (OS) of patients with ovarian cancer is poor while epithelial ovarian cancer (EOC) is the most lethal gynecologic cancer. The aim of the present study was to evaluate the clinico-pathologic characteristics, especially the prognostic factors, for patients with epithelial ovarian cancer (EOC) in Taiwan. Information about newly diagnosed patients with EOC from 2009 to 2012 was retrieved from the database of the Taiwan Cancer Registry. Data from 2009 to 2013 for the respective cases from the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
67
6
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 23 publications
11
67
6
3
Order By: Relevance
“…A change in the peak age at diagnosis from approximately 60 years old to 50 years old From 1979 to 2008 was reported in a study by Chiang et al 2 The mean age at diagnosis of the patients with EOC was reported as 52.8 years old in another study. 11 However, the mean age at diagnosis in the present study was 49 years old which was lower than those of the previously mentioned studies. 2,11 The percentage of ESEOC patients was 34.3% during the study period in the present study.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…A change in the peak age at diagnosis from approximately 60 years old to 50 years old From 1979 to 2008 was reported in a study by Chiang et al 2 The mean age at diagnosis of the patients with EOC was reported as 52.8 years old in another study. 11 However, the mean age at diagnosis in the present study was 49 years old which was lower than those of the previously mentioned studies. 2,11 The percentage of ESEOC patients was 34.3% during the study period in the present study.…”
Section: Discussioncontrasting
confidence: 84%
“…11 However, the mean age at diagnosis in the present study was 49 years old which was lower than those of the previously mentioned studies. 2,11 The percentage of ESEOC patients was 34.3% during the study period in the present study. The percentage of ESEOC patients in the current study was lower than a previous study which reported the percentage of earlystage patients as 44.4%.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Among malignant gynaecologic diseases, OC has the second highest incidence in Western countries after cervical cancer, and the third highest prevalence in Asian countries [3]. Prognostic factors for advanced OC include age, post treatment residual tumour volume, tumour histology, presence or absence of ascites, and serum CA-125 levels [4]. A combination of taxane and platinum-based therapies has been the standard treatment of OC for more than four decades.…”
Section: Introductionmentioning
confidence: 99%